Cooperation with Evil: Thomistic Tools of Analysis - Flannery, Kevin L. (Catholic University of America Press, 2019)
Intro -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- 1. Formal and Material Cooperation -- 2. Circumstances, Human Acts, and Indifference -- 3. Scandal -- 4. Factors in Reason and Justice: Part I -- 5. Factors in Reason and Justice: Part II -- 6. Concluding Ideas: Cooperation and Justice -- Appendix 1. Alphonsus Liguori, Theologia moralis, book 2, 59-67 -- Appendix 2. Alphonsus Liguori, Theologia moralis, book 3, 571 -- Appendix 3. Alphonsus Liguori, Theologia moralis, book 2, 43-45 -- Appendix 4. Thomas Aquinas, Quaestiones disputatae de malo, question 2, article 6 -- Appendix 5. Thomas Aquinas, Summa theologiae 2-2.64.7 -- Bibliography -- Index of References to Thomas Aquinas and Aristotle -- Index of Names -- Index of Subjects.